KEFIR GRAIN BIOMASS PRODUCTION: INFLUENCE OF DIFFERENT CULTURING CONDITIONS AND EXAMINATION OF GROWTH KINETIC MODELS - Apar, Dilek Kilic; Demirhan, Elcin; Ozel, Birsen; Ozbek, Belma (WILEY, 2017)
In this study, kefir grain biomass growth was investigated in whey enriched with some additives such as yoghurt, milk, glucose, sucrose, yeast extract and carob extract. The fermentation experiments were carried out at 27 degrees C for 10 days by refreshing the cultivation media at the end of each 24 h fermentation period. Maximum and minimum biomass increases were obtained as 1,438 and 836% in whey enriched with 5% (w/v) yeast extract and 10% (v/v) carob extract, respectively. Kefir biomass increase and fermentation kinetics were examined at different temperatures (17, 27, 37 degrees C) and different initial kefir grain concentrations (2.5, 5, 7.5%) for selected culture mediums (in whey and in whey enriched with milk and yoghurt). Optimum temperature and initial grain concentration for kefir biomass growth were obtained as 27 degrees C and 5% for all examined mediums. Modelling studies were performed and various kinetic models tested to represent the kefir biomass growth and fermentation kinetics. The convenience of the kefir biomass growth to the Monod kinetics was also examined.
Keywords: DRIED KEFIR; FERMENTATION EFFICIENCY; YEAST TECHNOLOGY; SCALE-UP; WHEY; STARTER; MILK; OPTIMIZATION; INCREASE; SYSTEM; Engineering; Food Science & Technology